Effect of Diameter on Steam Pressure Sootblower to Eliminate Low Potential Slagging and Fouling - Prabaswara, Abigail Qutratuain; Yuliyani, Ika; Widarti, Sri (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
The combustion process in pulverized coal boilers utilizes coal fuel, which produces ash and heat. Ash from combustion process will be deposited and adhere to pipes, known as slagging and fouling. Cleaning of slagging and fouling is done using a sootblower by flowing pressurized fluid to generate a jet nozzle force, which can remove the slagging and fouling adhering to the pipes in the superheater. Based on testing of parameters, ash fusion temperature is 1415.42 oC, and silica ratio is 79.55%, indicating a low potential for slagging. For fouling testing yielded an index of 0.089, indicating a low potential for fouling. The existing retractable sootblower operates using superheated steam with a pressure of 70-75 bar. In the design of low-pressure sootblower, flow is derived from intermediate pressure turbine by modifying feed tube, lance tube, and sootblower nozzle. The design results in a feed tube diameter of 101.65 mm, a lance tube diameter of 114.3 mm, an inlet nozzle diameter of 21.1 mm, a throat nozzle diameter of 13.97 mm, and an outlet nozzle diameter of 41.02 mm, with a Mach number output of 2.09 and a total jet force of 2023.9 N.